Radio Frequency Channel Coding Made Easy - Faruque, Saleh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces Radio Frequency Channel Coding to a broad audience. The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications. The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals.
Introduction to Channel Coding -- Automatic Repeat Request (ARQ) -- Block Coding -- Convolutional Coding -- Waveform Coding.
Keywords: Telecommunication; Computer networks .; Electronics; Communications Engineering, Networks; Computer Communication Networks; Electronics and Microelectronics, Instrumentation